2014
DOI: 10.1063/1.4858409
|View full text |Cite
|
Sign up to set email alerts
|

Photo-fragmentation spectroscopy of benzylium and 1-phenylethyl cations

Abstract: ) and 1-phenylethyl (C 6 H 5 -CH-CH 3 + )cations have been recorded via photofragment spectroscopy. Benzylium and 1-phenylethyl cations produced from electrosprayed benzylamine and phenylethylamine solutions, 1-phenylethyl cation also shows vibrational progressions. For both cations, the second electronic transition is observed in the UV, around 33 000 cm -1 (4.1 eV), and shows a broadened vibrational progression. In both cases the S 2 optimized geometry is non planar. The third electronic transition observed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 62 publications
(93 reference statements)
3
22
0
Order By: Relevance
“…28 Moreover, we have chosen the RI-CC2 method because it proved useful in describing the electronic transitions of similar aromatic ions with nitrogen functional groups. 29,30 In all the calculations the starting geometries had Cs symmetry and were constrained to distinguish between π or orbitals and A' or A'' excited states. In the case of the benzenediazonium ion fragment, adiabatic excitation energies were calculated in addition to the vertical excitation values.…”
Section: Methodsmentioning
confidence: 99%
“…28 Moreover, we have chosen the RI-CC2 method because it proved useful in describing the electronic transitions of similar aromatic ions with nitrogen functional groups. 29,30 In all the calculations the starting geometries had Cs symmetry and were constrained to distinguish between π or orbitals and A' or A'' excited states. In the case of the benzenediazonium ion fragment, adiabatic excitation energies were calculated in addition to the vertical excitation values.…”
Section: Methodsmentioning
confidence: 99%
“…The single gauche conformer is substantially stabilized with respect to the anti isomer by the additional intramolecular NH + ⋅⋅⋅π (cation–π) interaction between the positively charged ammonium group and the highly polarizable π electrons of the aromatic phenyl ring . For this reason, only the gauche conformer is populated in the gas phase, both in a cold molecular beam and at room temperature, that is, the cation–π interaction completely locks H + PEA in the gauche configuration, in stark contrast to neutral PEA (and o F‐PEA).…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50] Recent high-resolution experiments showed that rotational temperatures can reach down to 20-35 K (see Section VII C), while the trap is operated at 4.4 K. The biggest advantage of the 3D Paul trap is its ease of operation and its suitability for extracting ions for subsequent time-of-flight mass analyses. A number of cryogenic Paul traps have been built recently to conduct spectroscopy on cold ions, [71][72][73][74] in particular, Johnson and co-workers have developed it into a powerful cryogenic ion spectroscopy technique via H 2 tagging. [28][29][30] The current ESI Paul trap system at Brown University has been significantly improved over the first design.…”
Section: B the Cryogenic Paul Trapmentioning
confidence: 99%